Addressing Common Student Technical Errors in Field Data Collection: An Analysis of a Citizen-Science Monitoring Project - Joanna Philippoff (American Society for Microbiology, 2016)
The scientific value of citizen-science programs is limited when the data gathered are inconsistent, erroneous, or otherwise unusable. Long-term monitoring studies, such as Our Project In Hawai’i’s Intertidal (OPIHI), have clear and consistent procedures and are thus a good model for evaluating the quality of participant data. The purpose of this study was to examine the kinds of errors made by student researchers during OPIHI data collection and factors that increase or decrease the likelihood of these errors. Twenty-four different types of errors were grouped into four broad error categories: missing data, sloppiness, methodological errors, and misidentification errors. “Sloppiness” was the most prevalent error type. Error rates decreased with field trip experience and student age. We suggest strategies to reduce data collection errors applicable to many types of citizen-science projects including emphasizing neat data collection, explicitly addressing and discussing the problems of falsifying data, emphasizing the importance of using standard scientific vocabulary, and giving participants multiple opportunities to practice to build their data collection techniques and skills.